Cardiovascular safety trials of incretin‐based drugs: What do they mean?. Issue 3 (5th October 2016) - Yabe, Daisuke; Seino, Yutaka
Abstract : Results of EXAMINE, TECOS and ELIXA encourage neutral CV safety profiles of incretin‐based drugs in individuals with type 2 diabetes and established CV diseases or multiple CV risks; the heart failure findings of SAVOR‐TIMI53 are unexpected and very concerning. Moreover, LEADER results demonstrate benefits of liraglutide on preventing CV events in a similar study population. Abstract : Incretin‐based dipeptidyl peptidase‐4 inhibitors and glucagon‐like peptide‐1 receptor agonists are newer choices of antidiabetic medications that are now most widely used worldwide. Preclinical study results suggest that the two drugs potentially exert benefits to prevent onsets and/or progressions of diabetes‐related complications, such as myocardial infarctions and strokes. Outcomes of five clinical trials to evaluate the cardiovascular (CV) safety of dipeptidyl peptidase‐4 inhibitors and glucagon‐like peptide‐1 receptor agonist have been recently reported. The heart failure findings of the Saxagliptin Assessment of Vascular Outcomes Recorded in Patients with Diabetes Mellitus‐Thrombolysis in Myocardial Infarction 53 (SAVOR‐TIMI53) are unexpected and very concerning; results of the Examination of Cardiovascular Outcomes with Alogliptin vs Standard of Care (EXAMINE), the Trial Evaluating Cardiovascular Outcomes with Sitagliptin (TECOS) and the Evaluation of Lixisenatide in Acute Coronary Syndrome (ELIXA) encourage neutral CV safety profiles of incretin‐based drugs in individuals with type 2 diabetes and established CV diseases or multiple CV risks. Furthermore, the Liraglutide Effect and Action in Diabetes: Evaluation of Cardiovascular Outcome Results (LEADER) results show the benefits of liraglutide in preventing CV events in a similar study population. Despite the many preclinical studies showing the beneficial effects of incretin‐related drugs, most CV safety trials of incretin‐based drugs, except for LEADER, did not show benefits for CV events. It is important to recognize that CV safety trials were carried out to meet the US Food and Drug Administration guidance to assess CV safety of all new antidiabetic drugs; they were not designed to assess their benefits for CV events. Therefore, the long‐term potential benefit, as well as even the safety, of incretin‐based drugs for certain CV outcomes has not been definitively established, and requires evaluation in more specific and more relevant trials. If the need for CV safety trials would be determined based on an individual drug's safety data during its earlier development as well as its mechanism of action, resources could be saved for carrying out such clinical trials.